Lithium leach residue synthesis process of high crystallinity hydroxysodalite, NaX, NaA zeolites and solidification and migration of potentially toxic elements - Wang, Zongli; Luo, Xianli; Zheng, Xiaojun; Chen, Ming; Guo, Haifeng; Li, Qi (Arabian journal of chemistry, 2024)
Converting lithium leach residue (LLR) into zeolite can reduce environmental impacts while also producing high value-added products. However, the synthesis of zeolites by LLR under alkali fusion may result in the solidification and migration of potentially toxic elements with secondary environmental impacts. Systematic research into this subject is rare in the open literature and the mobility of toxic elements from LLR derived zeolites is yet to be understood. In this paper, we have investigated the highly crystalline synthesis of hydroxy sodalite, X-type zeolite (NaX), and A-type zeolite (NaA) without stencil agent and crystal species, which can be achieved by modulating the alkali fusion temperature, all three zeolites have greater than 90 % conversion of the major elements aluminum and silicon. Meanwhile, the leachability of thallium (Tl), beryllium (Be), and potentially toxic elements (lead (Pb), mercury (Hg), cadmium (Cd), chromium (Cr), arsenic (As), barium (Ba), copper (Cu), nickel (Ni), cobalt (Co), zinc (Zn)) was monitored by pH-dependent leaching test for LLR and three kinds of synthesized zeolites according to the Chinese standard and the emission of toxic elements during the synthesis process was analyzed, to investigate the migration and quantify the distribution of the toxic elements in the LLR to the product zeolites and the cleaning wastewater. The migration efficiency of potentially toxic elements from LLR to the product zeolite and cleaning wastewater was explored. It was found that most of the toxic elements Tl, Be and potentially toxic elements were solidified in the structure of the zeolites by ion exchange (solidification rate > 90 %), and a small portion flowed into the cleaning wastewater. Although there are toxic elements solidified in the structure, there is no significant leaching under various pH conditions, which is in line with the Chinese standard (GB/T 5085.3–2007). Therefore, it is considered that LLR realizes environmentally friendly zeolite production and does not cause secondary pollution to the environment. This work demonstrates great potential for green recycling of LLR from the lithium extraction process and introduces an environmentally friendly slag treatment technology.